(untitled) (Swiss Medical Weekly, 2011)
BACKGROUND: The indication for surgical treatment of a meniscal lesion should not only rely on magnetic resonance imaging (MRI) findings, but also on a detailed history and a thorough clinical examination. However, various intra-articular lesions may often produce similar symptoms. So, what kinds of symptoms are more associated with a meniscal tear? Is MRI worth doing? OBJECTIVE: The aims of this study were to identify sensitive and specific clinical tests and elements of patients’ history with a high predictive value, and to assess the combined diagnostic accuracy of sensitive and specific clinical tests and elements of patients’ history with MRI. METHODS: Data from 281 consecutive knee arthroscopies to investigate and treat suspected internal knee pathologies were retrospectively collected between March 2009 and April 2010. The study group consisted of 262 knees. Statistically significant factors in the clinical diagnosis of meniscal tears were screened by a chi-square test. Logistic regression analysis was used to determine which factors associated with meniscal tears found during arthroscopy. The diagnostic values of MRI and the sensitive and specific clinical tests and elements of patients’ history with high predictive value for meniscal tears were calculated. RESULTS: The overall diagnostic value of MRI for meniscal tears was: accuracy, 88.8%; sensitivity, 95.7%; specificity, 75.8%; positive predictive value (PPV), 88.2%; and negative predictive value (NPV), 90.4%. Giving way, locking and McMurray’s test were independent diagnostic factors with a predicted correct percentage of 80.0% (p<0.05) for the diagnosis of meniscal tears found during arthroscopy. Locking, McMurray’s test and MRI increased the predicted correct percentage of meniscal tears found during arthroscopy to 91.6% (p<0.05). For the diagnosis of meniscal tears found during arthroscopy, giving way, locking and McMurray’s test had the following values for accuracy (49.2, 60.9, 76), sensitivity (43.5, 55.2, 75.8), specificity (84, 96, 76.9), PPV (94.4, 98.8, 95.1) and NPV (19.4, 25.8, 35.1). Combining MRI, the diagnostic values of giving way, locking, and McMurray’s test were: accuracy, 88.3,89.9,89.4; sensitivity, 95.7,97.4,97.4; specificity, 74.2,75.8,74.2; PPV, 87.5,88.4,87.7; and NPV, 90.2,94,93.9. CONCLUSIONS: Giving way, locking and McMurray’s test are independent clinical diagnostic factors for the diagnosis of meniscal tears. MRI has higher accuracy, sensitivity and NPV for the diagnosis of meniscal tears than giving way, locking and McMurray’s test. The combination of giving way, locking, McMurray’s test and MRI for confirmation is typical for a meniscal lesion diagnosis. Based on these findings, MRI should be used in a standard manner to detect meniscal tears found during arthroscopy.